Improving feeding and growth of HIV-positive children through nutrition training of frontline health workers in Tanga, Tanzania - Bruno F. Sunguya; Linda B. Mlunde; David P. Urassa; Krishna C. Poudel; Omary S. Ubuguyu; Namala P. Mkopi; Germana H. Leyna; Anna T. Kessy; Keiko Nanishi; Akira Shibanuma; Junko Yasuoka; Masamine Jimba (BMC, 2017)
Abstract Background Nutrition training can boost competence of health workers to improve children's feeding practices. In this way, child undernutrition can be ameliorated in general populations. However, evidence is lacking on efficacy of such interventions among Human Immunodeficiency Virus (HIV)-positive children. We aimed to examine the efficacy of a nutrition training intervention to improve midlevel providers' (MLPs) nutrition knowledge and feeding practices and the nutrition statuses of HIV-positive children in Tanga, Tanzania. Methods This cluster-randomized controlled trial was conducted in 16 out of 32 care and treatment centers (CTCs) in Tanga. Eight CTCs were assigned to the intervention arm and a total of 16 MLPs received nutrition training and provided nutrition counseling and care to caregivers of HIV-positive children. A total of 776 pairs of HIV-positive children and their caregivers were recruited, of whom 397 were in the intervention arm. Data were analyzed using instrumental variable random effects regression with panel data to examine the efficacy of the intervention on nutrition status through feeding practices. Results Mean nutrition knowledge scores were higher post-training compared to pre-training among MLPs (37.1 vs. 23.5, p < 0.001). A mean increment weight gain of 300 g was also observed at follow-up compared to baseline among children of the intervention arm. Feeding frequency and dietary diversity improved following the intervention and a 6 months follow-up (p < 0.001). An increase in each unit of feeding frequency and dietary diversity were associated with a 0.15-unit and a 0.16-unit respectively decrease in the child underweight (p < 0.001). Conclusions Nutrition training improved nutrition knowledge among MLPs caring for HIV-positive children attending CTCs in Tanga, Tanzania. Caregivers' feeding practices also improved, which in turn led to a modest weight gain among HIV-positive children. To sustain weight gain, efforts should be made to also improve households' food security and caregivers' education in addition to inservice nutrition trainings. The protocol was registered on 15/02/2013, before the recruitment at ISRCTN trial registry with the trial registration number: ISRCTN65346364.